Assessing the evolution of infectious disease preparedness among a province with poor economy in China in the wake of COVID-19 - Huaying Liu; Qun Liang; Chen Lai; Huiping Liang (Frontiers in Public Health)
IntroductionTo identify the factors influencing changes in knowledge and experience of infectious disease prevention and control among physicians in Guangxis grassroots hospitals before and after the COVID-19 pandemic, thereby offering insights to enhance emergency response capabilities, disease prevention and control proficiency, and the overall effectiveness of grassroots medical institutions during epidemics.MethodsUtilizing random sampling, we conducted questionnaire surveys among primary care physicians from Guangxis primary medical institutions in June 2019 and October 2022, and analyzed the data with SPSS software.ResultsPost-COVID-19, there was a significant increase in the scores for theoretical knowledge (77.10 ± 14.83 vs. 63.10 ± 15.11, p < 0.001) and understanding of infectious disease regulations (54.78 ± 15.94 vs. 50.85 ± 12.52, p = 0.001) among grassroots hospital physicians compared to pre-COVID-19 levels, albeit with room for further improvement. The participation rate in emergency treatment of infectious diseases rose to 63.51% after COVID-19, from 58.33% of physicians lacking infectious disease training before the pandemic, which decreased to 35.60% post-pandemic. Currently, “community family medical observation” is the most sought-after training content among Guangxis grassroots physicians (31.25%).DiscussionThe capacity for infectious disease prevention and control among Guangxis grassroots hospital physicians has significantly improved following COVID-19. The high engagement in related training and emergency response efforts reflects a strong sense of professional identity and commitment. Ongoing, needs-based infectious disease training is recommended to ensure that grassroots medical staff can optimally contribute to the management of infectious disease emergencies.